Integrated Photonics: Scalable Functionalization of Optical Fibers Using Atomically Thin Semiconductors (Adv. Mater. 47/2020). Issue 47 (24th November 2020) - Ngo, Gia Quyet; George, Antony; Schock, Robin Tristan Klaus; Tuniz, Alessandro; Najafidehaghani, Emad; Gan, Ziyang; Geib, Nils C.; Bucher, Tobias; Knopf, Heiko; Saravi, Sina; Neumann, Christof; Lühder, Tilman; et al.
Abstract : Green lasers are coupled into nanostructured, exposed‐core fibers, functionalized with monolayer transition metal dichalcogenide crystals in a scalable chemical vapor deposition process by Antony George, Andrey Turchanin, Falk Eilenberger, and co‐workers in article number 2003826 . The laser light excites excitons in the monolayer, re‐emiting red photoluminescence into the fiber. Monolayer‐functionalized fibers may be a new path toward remote sensing and tailored nonlinearities.